Rapid and continuous regulating adhesion strength by mechanical micro-vibration - Langquan Shui (Nature Portfolio, 2020)
Controlled tuning of surface adhesion is crucial to a broad range of applications. By simply introducing a mechanical micro-vibration, Shui et al. discover that the surface adhesion can be either enhanced by orders of magnitude or weakened to zero with a switching rate at millisecond timescale.